Foundations For Diversifying Income Sources Through The Implementation Of Green Tourism At Historical And Cultural Heritage Sites In Bukhara Region - Khafizov, Abdulla Olimjonovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
this thesis analyzes the development of tourism and cultural heritage in the Bukhara region during the post-independence period, particularly focusing on the establishment of cooperation with UNESCO and other international organizations. The inclusion of Bukhara’s historical center (Poyi Kalon, Labi Hovuz, and the area surrounding Mir Arab) in the UNESCO World Heritage List in 1993 is highlighted as a crucial milestone in promoting the region internationally and institutionalizing tourism policies. The article discusses the unique value of Bukhara’s historical monuments and outlines strategies for implementing "green tourism" elements (such as pedestrian and bicycle paths, electric transport, efficient irrigation, and energy-saving lighting) in tourism development while preserving these cultural sites.